Postoperative structured nursing plan for patients with cervical spine fracture and spinal cord injury: a retrospective study - Ni Luo; Aijun Xu; Shanshan Xu; Bo Chen; Yunlin Chen; Xudong Hu; Jing Li (Frontiers in Surgery, 2026)
Objective This study aimed to examine the efficacy of structured nursing in promoting postoperative recovery among patients with cervical spine fracture and spinal cord injury. Methods This study is a retrospective cohort analysis. A total of 100 patients with cervical spine fracture and spinal cord injury who underwent anterior cervical discectomy and fusion (ACDF) at our Hospital from December 2023 to December 2025 were included as the research subjects. They were divided into control group (Routine nursing, n = 55) and observation group (Structured nursing, n = 45) according to actual nursing measures. Patients in the control group received routine care, while those in the observation group received structured nursing. Patients in both groups received nursing intervention until discharge. A comprehensive comparison was conducted between the two groups, covering the following aspects: psychological state, living function, motor function, cervical spine function, pain degree, quality of life, the incidence of complications during hospitalization, clinical efficacy, and nursing satisfaction. Results After patient care to discharge from hospital, the Self-Rating Depression Scale (SDS) and Self-Rating Anxiety Scale (SAS), Activities of Daily Living (ADL), and VAS scores in the structured nursing group were significantly lower than those in the normal group; while the FMA, JOA scores were significantly higher than those in the normal group. After nursing, the psychological, social, physical and material function scores of patients in both groups were higher than those before nursing, and the structured nursing group was higher than those in the normal group. The overall incidence of complications during hospitalization in the structured nursing group was 13.33%, which was significantly lower than that in the Routine nursing group (38.18%). Patients receiving structured nursing had better clinical outcomes and higher nursing satisfaction relative to the normal group. Conclusion Structured nursing can enhance the treatment outcome for patients with cervical spine fracture and spinal cord injury, alleviate pain and improve their negative emotions, and can also reduce the incidence of complications.